The national moroccan registry of ST-elevation myocardial infarction (MR-MI) - Aida Soufiani; Hamza Chraibi; Ilyasse Asfalou; Noha El Ouafi; Mustapha El Hattaoui; Rachida Habbal; Ali Chaib; Rokya Fellat; Hafid Akoudad; Aatif Benyass; Mohamed Cherti; Redouane Abouqal; et al. (BMC Cardiovascular Disorders, 2023)
Abstract Background MR-MI is the first national Moroccan ST-elevation myocardial infarction (STEMI) registry. Its objectives are to assess patient management modalities and highlight the clinical and therapeutic characteristics of this pathology in all cardiology centres on a national scale. Methods Adult patients presenting with STEMI within 5 days of symptoms onset were enrolled over a period of 18 weeks from April to August 2018. 57 cardiology centres distributed in 22 cities in Morocco participated in the study, including 5 university hospitals, representing 70% of Moroccan centres managing STEMI patients. A case report form was sent to the investigators in both electronic and paper forms. Sociodemographic, clinical, management, revascularization, and follow-up data were collected. Results A total of 809 patients were recruited. The population was mostly male (74.8%) with an average age of 62.6 ± 11.6 years. The most common risk factors were smoking (38.3%) arterial hypertension (30.7%), and diabetes (28%). 30% of patients were admitted within the first 6 h of symptoms onset and early revascularization was performed on 49.6%. Mortality rate was 5.2% in-hospital and 3.2% at the one-month follow-up. Conclusion MR-MI is the first Moroccan STEMI registry on a national scale. Relevant management delays are much longer than other countries, and less than 50% of the patients that present on time benefit from early revascularization. Efforts remain to be done on the optimal diagnosis and treatment of STEMI.